Legal Protection of Copyright - Natalya Vladivirovna Slesaryuk (Сибирское юридическое обозрение)
This article examines problems of legal regulation in the area of copyright in the context of inconsistency of present day legislation with modern realities. The author concludes that enhancement of protection of personal non-property copyright goes along with "commercialization" of property rights, which leads to an unjustified restriction of freedom of information. The author attempts to find out possibilities of improving the Russian civil law in the area of copyright.